ANALISIS BIBLIOMETRIK PENELITIAN ETNOMEDISIN - Muslihin, A.M.; Hardia, Lukman (JURNAL ETNOFARMASI, 2024)
Ethnomedicine is the study of certain communities in using medicines. Information on the use of medicinal plants can be provided using an ethnomedicine approach. Ethnomedicine as a method that can be used to explore the use of medicinal plants can be the first step to developing new medicines. Knowledge about how to process traditional ingredients used in certain community groups can be used as a reference in developing medicinal raw materials. Research on the use of medicinal plants in various communities (cross-cultural studies) can be used to find drugs and bioactive compounds. Ethnomedicine is an important stage in screening, selecting and developing new medicines derived from plants. Ethnic communities in an area have unique culture and local wisdom due to regional differences. This has an impact on knowledge about traditional medicine and medicine. Various tribes or ethnic groups in Indonesia have their own experiences in dealing with health problems. Ethnomedicine is part of a community's traditional medicine, often empirically proven, scientifically validated, for the discovery or development of new medicinal compounds.